Physical Test Results of Used Cooking Oil Using Mangrove Activated Carbon - Ratni Sirait; Masthura Masthura; Wulandari Armaya Sembiring (Lambung Mangkurat University Press, 2023)
Cooking oil is a human need and has a close relationship with our physical health. Cooking oil is used repeatedly, the color and smell of the oil can change at high temperatures. In this study, used cooking oil can be reused by using adsorbents and materials used for mangrove-activated carbon. The purpose of this study was to determine the test results of used cooking oil before and after the adsorbent. This experiment uses the adsorption method with activation temperature variations of 500℃, 600℃, and 700℃. There are several test parameters, namely Odor, Color, and Moisture Content. The test results show the quality of used cooking oil at an activation temperature of 500℃ obtained Normal Odor, Color: Red 8.1, Yellow 14.0 and Blue 4.8, Water Content 0.07% according to SNI 7709.2019.